The newcomer - Andrews, Mary Kay, 1954- (Waterville, ME : Thorndike Press, a part of Gale, a Cengage Company, 2021)
After she discovers her sister Tanya dead on the floor of her fashionable New York City townhouse, Letty Carnahan is certain she knows who did it: Tanya's ex; sleazy real estate entrepreneur Evan Wingfield... So Letty grabs her sister's Mercedes and hits the road with her wailing four-year-old niece Maya. Letty is determined to out-run Evan and the law, but run to where?
Keywords: Sisters -- Death -- Fiction; Murder -- Fiction; Nieces -- Fiction; Grief -- Fiction; Justice -- Fiction; Runaway women -- Fiction; Motels -- Fiction; Florida -- Fiction; Large type books; Thrillers (Fiction); Romance fiction